Improving Speaking Skills Through Role-Playing Activities Based on Fairy Tales - Rike Komala Sari; Yusi Puji Pamusti; Dede Endang Mascita; Mudopar (MIMBAR PGSD Undiksha, 2025)
Learning processes that remain dominated by teacher-centered instruction often limit students’ opportunities to engage in active verbal interaction, resulting in underdeveloped speaking abilities. This condition highlights the need for more exploratory and participatory learning approaches that allow students to construct oral communication meaningfully. This study aims to analyze the effectiveness of a storytelling-based role-playing activity using character masks in enhancing students’ speaking skills. The research employed a quasi-experimental method with a one-group pre-test–post-test design involving 21 elementary students as research subjects. Data were collected through a speaking performance test, classroom observations, and documentation, with instruments validated through content validation by expert judgment. Data were analyzed using descriptive statistics, paired sample t-test, and N-Gain analysis. The findings indicate that the role-playing activity substantially improved students’ speaking performance, as reflected in a significant score increase from pre-test to post-test, categorized as highly effective based on the N-Gain value. These results imply that storytelling-based role play can serve as a relevant pedagogical strategy to strengthen students’ speaking proficiency while simultaneously promoting greater engagement in the learning process.